Synovectomy of the elbow and radial head excision in rheumatoid arthritis. Predictive factors and long-term outcome. - Gendi, N; Axon, J; Carr, A; Pile, K; Burge, P; Mowat, A (1997)
We carried out a survival analysis of elbow synovectomy (ES) and excision of the radial head (RHE) performed on 171 rheumatoid elbows. The failure criteria were revision surgery (performed or desired) and/or the presence of significant or severe pain. The cumulative survival was 81% at one year which thereafter decreased by an average of 2.6% per year. The strongest predictor for success was a low preoperative range of supination-pronation when corresponding survival curves were compared. A low range of flexion-extension also predicted failure. Combining both factors gave better prediction (failure: 6.3% v 67%), but a long duration of elbow symptoms before surgery predicted failure (72%, p = 0.04). At review, there was a mean gain of 50 degrees in supination-pronation and 11 degrees in flexion-extension; both correlated with success. Failure correlated with recurrence of synovitis, elbow instability, ulnar neuropathy, poor general mobility and poor upper-limb function. The last was independently affected by the severity of RA in the ipsilateral shoulder. Our findings show that although the short-term result of ES and RHE in rheumatoid arthritis is good, the long-term outcome is poor except in a subgroup with more than 50% limitation of forearm rotation.